Elevated Specific Pro-Inflammatory Cytokines in Peripheral Circulation Indicate an Increased Risk of Anxiety and Depression in Rosacea - Yang X; Feng Z; Cai M (Dove Medical Press, 2024)
Xiaoting Yang,1 Zuxing Feng,2 Mei Cai1 1Department of Dermatology and Venereology, The Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, 650101, People's Republic of China; 2Department of Psychiatry, The Psychiatry Hospital of Yunnan, Kunming, Yunnan, 650224, People's Republic of ChinaCorrespondence: Mei Cai, Department of Dermatology and Venereology, The Second Affiliated Hospital of Kunming Medical University, No. 374, Yunnan-Myanmar Avenue, Kunming, Yunnan, 650101, People's Republic of China, Tel +86 13888532488, Email caimei5867@163.comObjective: Pro-inflammatory cytokines mediate the course of rosacea, anxiety, and depression through various means such as immunity and inflammation. This study aims to further explore the relationship between rosacea, anxiety, and depression through changes in the levels of pro-inflammatory cytokines.Methods: 280 rosacea patients were included in the rosacea group, divided into: rosacea without mental disorders, rosacea with anxiety, rosacea with depression, and rosacea with combined anxiety and depression. The mental control group included 210 anxiety and depression patients, divided into: anxiety, depression, and combined anxiety and depression. The healthy control group consisted of 70 healthy individuals. Serum specimens were collected and ELISA was used to detect major pro-inflammatory cytokines. CEA, IGA, GFSS, RosaQoL, HAMA, and HAMD-24 were used for the diagnosis and severity assessment of rosacea and anxiety and depression.Results: This study primarily used the Chi-Square test, Kruskal-Wallis H-test, generalized linear model, and binary logistic regression to evaluate the data. IL-1β, IL-17, and IL-8 levels in rosacea patients and anxiety/depression patients were higher than those in the healthy population (P< 0.001), and TNF-α levels in rosacea patients were higher than those in the healthy population (P< 0.001). There was an interaction between rosacea, anxiety, and depression in terms of IL-1β, IL-17, and IL-8 levels (P< 0.001). Elevated levels of IL-1β, IL-17, and IL-8 are positively correlated with anxiety and depression in rosacea (all P